KARAKTERISTIK FISIK HABITAT LEDA (Eucalyptus deglupta) DI JALUR PENDAKIAN GUNUNG NOKILALAKI KAWASAN TAMAN NASIONAL LORE LINDU - Annisah, Nur; Sudhartono, Arief; Ramlah, Sitti (Jurnal Warta Rimba, 2014)
Leda (Eucalyptus deglupta) is one kind of endemic flora of Celebes that its natural spread area side on Lore Lindu National Park (LLNP). The aim of this research was pointed to investigate the physiccally charracteristic of Leda habitat. The usage of this research is hoped to enrich scientific information in order to improve understanding about charracteristic of Leda habitat. This research was conducted in highing track of Nokilalaki Mount – LLNP territory, Nokilalaki District – Sigi Regency, as long as two months (October up to December 2013) used survay methode and laboratory analysis, by the placement of 7 (seven) sampling plots used purposive sampling methode at the location where be found habitat of Leda based on the high from sea level. Getting of soil samples used soil sample rings,than be analyzed on soil textures, permeabilities, bulk densities, and soil porousities.This research results shown that the charracteristic of Leda habitat in highing track of  Nokilalaki Mount be located on (1110-1206) meters from sea level high, with land slope (8-15)% (enough obliquity), the temperature on morning time (19-20)°C and afternoon time (19-23)°C, the air moisture on morning time (81-90)% and afternoon time (76-91)%, intensity of sun shine (80-400) lux. Physiccally charracteristic of soil texture are clay-clayey-sandy, clay-sandy, clayey-sandy, and clayey. Soil permeabilities (15.05-47.61) cm/hour (Fast andVery Fast catagories). Bulk density (0.91-1.27) g/cm3 (Fair and High catagories) and porousity (51.92-65.61)%. Kata Kunci : habitat, Leda, Lore-Lindu, Nokilalaki, physiccally-charracters.